The Effect of Lemon Aromatherapy on Decreasing Perineum Pain among Postpartum Women at Noah Arofah Medika Clinic Bekasi District in 2020 - Rianti, Ririn; Rukmaini; Rifiana, Andi Julia (Journal of Global Research in Public Health, 2020)
The puerperium period is a period that starts a few hours after the birth of the placenta until 6 weeks after delivery when the uterus organs return to their pre-pregnancy state. After vaginal delivery, a women often feels pain and trauma to the perineum. Perineal pain is pain that results from a tear that occurs in the perineum, vagina, cervix, or uterus that can occur spontaneously or as a result of manipulative action on delivery assistance. The effects of perineal pain are making the post partum women uncomfortable, having a bad effect on the mother's desire to breastfeed her baby, experiencing fear of early mobilization so that it can cause problems and complications during the puerperium such as sub-uterine involution, non-smooth discharge, infection and post-partum hemorrhage. This will increase the morbidity and mortality rates for mothers in Indonesia. One of the non-pharmacological pain management methods is using aromatherapy. Lemon aromatherapy is a type of aromatherapy that can be used to treat pain and disease. Substances contained in lemon one of which is linalool is useful for stabilizing the nervous system so that it can have a calming effect for anyone who inhales it. This study aims to determine the effect of lemon aromatherapy on reducing perineal pain among postpartum women at Noah Arofah Medika Clinic, Bekasi Regency. The design of this study used the Quasy Experimental Design method with the research design of The Non-equivalent Control Group Design. The sample in this study were 20 respondents. The sampling technique used is the Accidental Sampling technique. The results of the study using the Independent T-test showed that there was a statistically significant effect of lemon aromatherapy on reducing perineal pain among postpartum women with a p value of 0.007 (p <0.05). Lemon aromatherapy is effective in reducing the scale of perineal pain in postpartum women. Therefore, lemon aromatherapy should be applied as an alternative intervention in carrying out midwifery care that is used to reduce perineal pain